Better Understanding in the Differentiation of Thyroid Follicular Adenoma, Follicular Carcinoma, and Follicular Variant of Papillary Carcinoma: A Retrospective Study. (18th September 2014) - Yoon, Jung Hyun; Kim, Eun-Kyung; Youk, Ji Hyun; Moon, Hee Jung; Kwak, Jin Young
Abstract : Background. To evaluate the role of ultrasonography (US), US-guided fine-needle aspiration (USFNA) and intraoperative frozen section (FS) in follicular neoplasm. Methods . US features, USFNA cytology, and FS results were compared based on the pathology results of patients with follicular adenoma (FA), follicular carcinoma (FC), and follicular variant of papillary thyroid carcinoma (FVPTC). Results . FC and FVPTC showed significantly higher rates of suspicious US features (P < 0.05 ) and positive findings on either US or cytology, 80.0% and 90.7%, compared to FA, 64.5% (P = 0.001 ). Intraoperative FS showed higher malignant rates in FVPTC and FC (81.8% and 75.0%, resp.), compared to FA (3.8%, P < 0.001 ). Conclusion . Suspicious US features were more significantly seen in FC and FVPTC compared to FA. Intraoperative FS is useful in the differential diagnosis of these lesions and supplements cytology results of USFNA.